Neutrophil CD64 index: a novel biomarker for risk stratification in acute pancreatitis - Shao, Min; Wu, Ling; Huang, Xiangping; Ouyang, Qianhui; Peng, Ya; Liu, Sixiang; Xu, Xu; Yi, Qi; Liu, Yi; Li, Guoguang; Ning, Ding; Wang, Jia; et al. (Frontiers in Immunology, 2025)
ObjectiveEffective early diagnosis and timely intervention in acute pancreatitis (AP) are essential for improving patient outcomes. This study aims to evaluate the clinical utility of the neutrophil CD64 index (nCD64) in stratifying patients with SAP and assessing mortality risk.MethodsA total of 302 AP patients were enrolled and divided into a training cohort (n = 226) and a validation cohort (n = 76). Venous blood samples were collected within 24 hours of admission, and the nCD64 index was measured via flow cytometry. Other clinical parameters, including C-reactive protein (CRP) and procalcitonin (PCT), were also recorded. Logistic regression and receiver operating characteristic (ROC) curve analyses were performed to assess the diagnostic value of the nCD64 index and its capacity to predict mortality risk.ResultsROC curve analysis identified a cutoff value of 1.45 for the nCD64 index. Patients with nCD64 > 1.45 had significantly higher risks of complications, including systemic inflammatory response syndrome (SIRS), acute respiratory distress syndrome (ARDS), multiple organ failure (MOF), and death. Over 65% of patients with acute pancreatitis (AP) can be effectively risk-stratified at a low cost, and it has been demonstrated that AP patients with an nCD64 value ≤ 1.45 have an extremely low mortality rate (no mortality in present training and validation cohort). Kaplan-Meier survival analysis revealed a significant survival difference between high-risk (nCD64 > 1.45) and low-risk groups (p < 0.001).ConclusionThe nCD64 index is an effective tool for early identification of SAP patients, allowing for the classification of over 65% of cases as low-risk for mortality.